Preparation method and application of silicon quantum dot water treatment agent with corrosion and scale inhibition performance
By using silicon quantum dot water treatment agent prepared by trisodium citrate, carboxymethylcellulose and trimethylsilimidazole, the problem of lack of multifunctional quantum dot corrosion inhibitors in the prior art with both corrosion inhibition and scale resistance is solved, and efficient corrosion inhibition and scale resistance is achieved, especially in inhibiting calcium sulfate scale, it shows extremely high efficiency.
Patent Information
- Application Number
- CN202510241324.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-03
AI Technical Summary
When solving the problems of metal corrosion and scale formation in circulating cooling water systems, existing water treatment agents lack multifunctional quantum dot corrosion inhibitors with both corrosion inhibition and scale resistance, and silicon quantum dots have been studied in the field of water treatment technology.
Using trisodium citrate, carboxymethylcellulose and trimethylsilimidazole as raw materials, surface carboxylated and hydroxylated silicon quantum dot water treatment agent is prepared by optimizing the process parameters of the hydrothermal method to achieve its corrosion inhibition and scale inhibition effects under neutral and acidic conditions.
The prepared silicon quantum dot water treatment agent has the dual functions of high-efficiency corrosion inhibition and scale inhibition, especially in inhibiting calcium sulfate scale, it has a 99.99% efficiency and is good in water solubility. It is suitable for a wide range of metal or alloy surfaces.
Smart Images

Figure CN119841472A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water treatment agent preparation, and specifically relates to a preparation method and application of a silicon quantum dot water treatment agent with corrosion and scale inhibition performance. Background Art
[0002] During the operation of the circulating cooling water system, deposits (scale) often accumulate on the metal surface of the cooling equipment. Most cooling equipment, such as heat exchangers, are made of carbon steel. The presence of deposits will greatly reduce the cooling effect of the heat exchanger and create the necessary conditions for under-scale corrosion. Water treatment agents with excellent corrosion and scale inhibition properties can not only effectively inhibit the scaling and corrosion of circulating cooling water, save circulating cooling water consumption, but also extend the service life of equipment.
[0003] The water treatment agent solutions are mostly: phosphorus-based, zinc-based, and fully organic formulas, among which phosphorus-based ones account for the largest proportion.
[0004] In the past five years, non-metallic quantum dots have been widely used in the field of metal corrosion and protection due to their unique biocompatibility and photochemical properties. Non-metallic quantum dot water treatment agents are mainly carbon quantum dots, which are modified with nitrogen, sulfur elements or functional groups on the surface to form coordination compounds with metal ions, thereby achieving the effect of delaying metal corrosion and scale formation. Compared with carbon, silicon has excellent corrosion inhibition properties, and traditional silicon-based corrosion inhibitors have been widely used. Therefore, modified silicon quantum dots are more suitable for use as water treatment agents, but in fact, there are not many studies on silicon quantum dot water treatment agents, and even fewer have practical application value.
[0005] The method to control corrosion and scaling is to add corrosion inhibitors and scale inhibitors to cooling water. Scale inhibitors focus on solving problems such as reduced heat transfer efficiency and equipment blockage caused by scale formation. Corrosion inhibitors: are suitable for occasions where metal equipment needs to be protected from corrosion. In water treatment systems containing corrosive media (such as acids, alkalis, salts, etc.), the use of corrosion inhibitors can effectively extend the service life of the equipment. However, the development and research of traditional water treatment agents usually does not focus on their additional functions beyond testing a single performance, so there is currently little research on multifunctional water treatment agents. Comprehensively considering the characteristics of different water treatment agents, targetedly regulating and designing the structure of corrosion inhibitors and scale inhibitors, and preparing composite agents that integrate multiple functions are key technologies that are lacking in the application of water treatment agents in actual industrial circulating cooling water systems, and are urgently in need of dedicated research by relevant researchers.
[0006] At present, non-metallic environmentally friendly quantum dot corrosion inhibitors represented by carbon quantum dots have been widely studied. However, the research on multifunctional quantum dot corrosion inhibitors with both corrosion and scale inhibition properties still needs further exploration. Therefore, silicon quantum dots are used in the field of water treatment technology in order to achieve better technical effects. Such research is rare at home and abroad, and even fewer have practical application value. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a silicon quantum dot water treatment agent with corrosion and scale inhibition properties. The silicon quantum dot water treatment agent is prepared by using trisodium citrate, carboxymethyl cellulose and trimethylsilyl imidazole as raw materials by optimizing the hydrothermal process parameters. The silicon quantum dot water treatment agent can be applied to carbon steel under neutral and acidic conditions to achieve the purpose of corrosion inhibition, and can effectively inhibit calcium scale in solutions that are prone to form calcium sulfate scale and calcium carbonate scale.
[0008] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a silicon quantum dot water treatment agent with corrosion and scale inhibition performance comprises the following steps: S1: Disperse the silicon source, modifier and reducing agent in ultrapure water, mix and stir for 35-55 minutes to obtain a mixed solution; S2: transferring the mixed solution obtained in step S1 to a hydrothermal reaction vessel for reaction to obtain a silicon quantum dot solution; S3: Centrifuge the silicon quantum dot solution obtained in step S2, purify, and freeze-dry to obtain a solid silicon quantum dot water treatment agent.
[0009] Furthermore, in step S1, the mass ratio of the silicon source, the modifier and the reducing agent is 5-7:1:1; and the solid-liquid ratio of the silicon source and ultrapure water is 2-4g:10ml.
[0010] Furthermore, the silicon source is trimethylsilyl imidazole, the modifier is one of carboxymethyl cellulose, gum arabic or chitosan, and the reducing agent is trisodium citrate.
[0011] Furthermore, in step S2, the reaction is carried out at a temperature of 210-230° C. for 2-6 hours.
[0012] Furthermore, the characteristics of the silicon quantum dots in step S2 are that the structure is surface carboxylated and hydroxylated silicon quantum dots; the lattice spacing is 0.19 nm, and the average diameter is 3.56 nm; indicators: it has the dual functions of corrosion inhibition and scale inhibition, and the efficiency of calcium sulfate scale inhibition is very high. When the addition amount is only 6 mg / L, the inhibition efficiency of calcium sulfate scale reaches 99.99%, and the water solubility is good.
[0013] Furthermore, the process parameters of the centrifugation in step S3 are: centrifugation rate 5000-10000 rpm, centrifugation time 10-30 min.
[0014] Furthermore, the purification process in step S3 is: dialyzing for 24-36 hours using a dialysis bag with a cutoff of 800-1500 Da; and the drying process is: drying at a temperature of -50°C for 48-60 hours.
[0015] The above silicon quantum dot water treatment agent is used for corrosion inhibition of carbon steel under neutral and acidic conditions. The silicon quantum dot water treatment agent is applied to the surface of the metal substrate of Q235 carbon steel in a 3.5wt% NaCl solution and a 0.5 mol / L HCl environment. The dosage of the silicon quantum dot water treatment agent is 20-100 mg / L.
[0016] The silicon quantum dot water treatment agent is used in a solution that is prone to calcium sulfate scale formation, and 0.5-6 mg / L of the silicon quantum dot water treatment agent is added to the solution that is prone to calcium sulfate scale formation.
[0017] The silicon quantum dot water treatment agent is used in a solution that is prone to forming calcium carbonate scale, and 5-150 mg / L of the silicon quantum dot water treatment agent is added to the solution that is prone to forming calcium carbonate scale.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention uses trisodium citrate, carboxymethyl cellulose and trimethylsilyl imidazole as raw materials, combines the inherent properties of silicon itself such as good biocompatibility, environmental friendliness and low price, and the characteristics of carboxymethyl cellulose with good corrosion inhibition effect and good water solubility, adopts a simple hydrothermal method to synthesize blue silicon quantum dots in one step, and innovatively uses them in the field of water treatment technology. The above raw materials are cheap and easy to obtain, the operation is green and environmentally friendly, and it is easy to mass produce in factories. The characteristics of the silicon quantum dots prepared by the present invention are: surface carboxylation and hydroxylation of silicon quantum dots The lattice spacing is 0.19 nm, and the average diameter is 3.56 nm. It has the dual functions of corrosion inhibition and scale inhibition. The calcium sulfate scale inhibition efficiency is very high. When the dosage is only 6 mg / L, the inhibition efficiency of calcium sulfate scale is 99.99%, and it has good water solubility.
[0019] 2. The water treatment agent of the present invention has a wide range of uses and has a good corrosion and scale inhibition effect on common metal or alloy surfaces in complex polluted environments.
[0020] 3. When the silicon quantum dot water treatment agent is added to a concentration of 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 93.68% when immersed in a 0.5 mol / L HCl environment; the corrosion inhibition efficiency is 93.33% when immersed in a 3.5 wt.% NaCl solution; it has a significant inhibitory effect on the corrosion of hydrochloric acid and sodium chloride.
[0021] 4. When the silicon quantum dot water treatment agent of the present invention is added at a concentration of 6 mg / L, the inhibition efficiency of calcium sulfate scale is 99.99%; when the addition concentration is 150 mg / L, the inhibition efficiency of calcium carbonate scale is 26.45%; it has a certain inhibitory effect on the formation of two types of calcium scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the preparation process of silicon quantum dot water treatment agent; Figure 2 Characterization diagram of silicon quantum dot water treatment agent: transmission electron microscopy images (a, b), high-resolution transmission electron microscopy image (c), particle size distribution diagram (d); Figure 3 This is the infrared spectrum of silicon quantum dots; Figure 4 This is the experimental graph of weight loss of Q235 steel by silicon quantum dots in 0.5 mol / L HCl solution; Figure 5 This is the experimental graph of weight loss of Q235 steel by silicon quantum dots in 3.5 wt.% NaCl solution; Figure 6 The potentiodynamic polarization curve of silicon quantum dots on Q235 steel in 0.5 mol / L HCl solution; Figure 7 The potentiodynamic polarization curve of silicon quantum dots on Q235 steel in 3.5 wt.% NaCl solution; Figure 8 This is a scale inhibition test diagram of silicon quantum dot water treatment agent for calcium sulfate and calcium carbonate; Fig. 9 These are scale diagrams after the silicon quantum dot water treatment agent scale inhibition test: comparison of changes in calcium sulfate scale before and after adding the silicon quantum dot water treatment agent (a, b); comparison of changes in calcium carbonate scale before and after adding the silicon quantum dot water treatment agent (c, d). DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The sources used in the present invention are as follows: The reagents used, unless otherwise specified, can be purchased from conventional biochemical reagent companies, and ultrapure water is used to prepare all aqueous solutions. Q235 carbon steel was obtained from Jiangsu Gaoyou Motian Co., Ltd. (China), and its chemical composition (by weight percentage) is as follows: carbon 0.17%; manganese 0.37%; silicon 0.20%; sulfur 0.03%; phosphorus 0.01%, and the rest is iron. Before the test, the samples were mechanically polished with silicon carbide paper with a particle size of 300, 1000 and 1500, then cleaned with acetone and vacuum dried for use.
[0025] Example 1
[0026] This embodiment provides a method for preparing a silicon quantum dot water treatment agent, comprising the following steps: S1: Dissolve 1.8 g trisodium citrate and 1.8 g carboxymethyl cellulose in 48 mL ultrapure water, and add 12 mL trimethylsilyl imidazole dropwise under stirring to obtain a mixed solution; S2: transferring the mixed solution obtained in step S1 into a hydrothermal reactor, performing a hydrothermal reaction at 220° C. for 2 h, and then cooling to room temperature to obtain a silicon quantum dot solution; S3: The silicon quantum dot solution obtained in step S2 is transferred to a centrifuge at a centrifugal speed of 5000 rpm for 10 min; after removing solid impurities, the supernatant is taken and dialyzed with a 1000 Da dialysis bag for 24 h; after the dialysis is completed, it is transferred and freeze-dried at a temperature of -50°C for 48 h; finally, the product silicon quantum dot water treatment agent is obtained and stored at 4°C for use.
[0027] Example 2
[0028] This embodiment provides a method for preparing a silicon quantum dot water treatment agent, comprising the following steps: S1: Dissolve 1.8 g trisodium citrate and 1.8 g carboxymethyl cellulose in 48 mL ultrapure water, and add 12 mL trimethylsilyl imidazole dropwise under stirring to obtain a mixed solution; S2: transferring the mixed solution obtained in step S1 into a hydrothermal reactor, performing a hydrothermal reaction at 220° C. for 2 h, and then cooling to room temperature to obtain a silicon quantum dot solution; S3: The silicon quantum dot solution obtained in step S2 is transferred to a centrifuge at a centrifugal speed of 6000 rpm for 15 min; after removing solid impurities, the supernatant is taken and dialyzed with a 1000 Da dialysis bag for 36 h; after the dialysis is completed, it is transferred and freeze-dried at a temperature of -50°C for 60 h; finally, the product silicon quantum dot water treatment agent is obtained and stored at 4°C for use.
[0029] Example 3
[0030] This embodiment provides a method for preparing a silicon quantum dot water treatment agent, comprising the following steps: S1: Dissolve 1.8 g trisodium citrate and 1.8 g carboxymethyl cellulose in 48 mL ultrapure water, and add 12 mL trimethylsilyl imidazole dropwise under stirring to obtain a mixed solution; S2: transferring the mixed solution obtained in step S1 into a hydrothermal reactor, performing a hydrothermal reaction at 220° C. for 2 h, and then cooling to room temperature to obtain a silicon quantum dot solution; S3: The silicon quantum dot solution obtained in step S2 is transferred to a centrifuge at a speed of 5800 rpm for 12 min. After removing solid impurities, the supernatant is taken and purified by dialyzing with a 1000 Da dialysis bag for 30 h. After the dialysis is completed, the solution is transferred and freeze-dried at a temperature of -50°C for 52 h. Finally, the product silicon quantum dot water treatment agent is obtained and stored at 4°C for later use.
[0031] Example 4
[0032] The difference from Example 1 is that the modifier is gum arabic, and the other steps are the same. When the concentration is 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 93.28% when immersed in 0.5 mol / L HCl environment; the corrosion inhibition efficiency is 89.02% when immersed in 3.5wt.% NaCl solution; it has a significant inhibitory effect on the corrosion of hydrochloric acid and sodium chloride.
[0033] Example 5
[0034] The difference from Example 1 is that the modifier is chitosan, and the other steps are the same. When the concentration is 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 63.95% when immersed in 0.5 mol / L HCl environment; the corrosion inhibition efficiency is 70.61% when immersed in 3.5wt.% NaCl solution; it has a significant inhibitory effect on the corrosion of hydrochloric acid and sodium chloride.
[0035] The silicon quantum dots obtained in Example 1 were characterized by FTIR and TEM. Figure 2The transmission electron micrographs of water-soluble silicon quantum dots are shown in Figures a and b. It can be concluded that the silicon quantum dots are evenly distributed; from Figure c, it can be seen that the high-resolution transmission electron micrograph shows that the lattice spacing of the silicon quantum dots is 0.19 nm, indicating that it has excellent crystallinity; from Figure d, it can be concluded that based on the measurement and calculation of 110 particles, the average diameter of the silicon quantum dots is 3.56 nm.
[0036] like Figure 3 The infrared spectrum of the water-soluble silicon quantum dots prepared in Example 1 shows: FTIR (KBr), ν: 3440, 2935, 1650, 1155 and 1078 cm -1 3440 cm -1 The absorption peak at 2935 cm indicates the presence of -OH and -NH2 groups on the surface of silicon quantum dots; -1 The absorption peak at 1650 cm -1 The peaks at 1115 and 1078 cm -1 The observed absorption peaks indicate the presence of COC / Si-O-Si bonds. These findings reveal that the surface of silicon quantum dots contains abundant hydroxyl and carboxyl groups, and these functional hydrophilic groups significantly enhance their solubility in water and their anti-scaling and anti-corrosion properties.
[0037] The corrosion and scale inhibition performance test of the silicon quantum dot water treatment agent prepared in Example 1, the test method used is as follows: (1) Corrosion inhibition performance study - static weight loss The static weight loss method was used to evaluate the corrosion inhibition performance of the silicon quantum dot water treatment agent, and the corrosion weight loss test was carried out in accordance with the national standard GB 10124-88 "Method for laboratory uniform corrosion full immersion test of metal materials".
[0038] The experimental material is Q235 carbon steel, and the size of the test piece is 5.0 × 2.5 × 0.2 cm. The test piece is polished with sandpaper, treated with anhydrous ethanol, blown dry and weighed, and the initial mass of the carbon steel is recorded. The weighed test piece is statically suspended in a blank and a circulating water solution with different corrosion inhibitor concentrations, soaked for 24 hours, taken out, cleaned, blown dry and weighed, and the mass after corrosion is recorded. According to the mass difference before and after, the corrosion rate, corrosion inhibition efficiency and surface coverage are calculated.
[0039] (2) Potentiodynamic polarization curve measurement The electrochemical test was carried out in a 0.5 mol / L hydrochloric acid solution containing different concentrations of silicon quantum dots. The hydrochloric acid solution without corrosion inhibitor was used as a blank control, and the temperature was controlled by a constant temperature water bath. A saturated calomel electrode (SCE) was used as the reference electrode, a platinum electrode was used as the auxiliary electrode, and a carbon steel electrode was used as the working electrode. Before the electrochemical test, the three-electrode system was immersed in the test solution and the open circuit potential was stabilized to ensure that the feedback of the electrochemical signal only depended on the liquid-solid interface state and to exclude interference from adverse external factors. The scanning range of the potentiodynamic polarization curve was -700 ~ -150 mV, and the scanning rate was 1.0 mV·s -1 , the scanning direction is from negative to positive.
[0040] (3) Study on scale inhibition performance - static scale inhibition The static scale inhibition method was used to evaluate the scale inhibition performance of the silicon quantum dot water treatment agent. The inhibition test of calcium sulfate was carried out in accordance with the national standard GB / T 16632-2019 "Determination of Scale Inhibition Performance of Water Treatment Agents-Calcium Carbonate Deposition Method", and the inhibition test of calcium carbonate was carried out in accordance with the industry standard SY / T 5673-2020 "General Technical Conditions for Scale Inhibitors for Oil Fields".
[0041] After adding the scale inhibitor, the scale formation process in the water body can be inhibited, that is, the amount of calcium sulfate or calcium carbonate precipitation will be reduced, and the concentration of free calcium ions in the water body will be higher than that of calcium ions in the water body without adding the scale inhibitor. The scale inhibition rate can be calculated based on the changes in the concentration of calcium ions in the blank water sample before and after the experiment and in the water sample after adding the scale inhibitor.
[0042] The silicon quantum dot water treatment agent prepared in Example 1 was added to 0.5 mol / L HCl solution and 3.5wt.% NaCl solution, respectively, to prepare corrosion inhibitor solutions with concentrations of 20, 40, 60, 80, and 100 mg / L. The treated carbon steel substrate was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and platinum was used as the counter electrode to be placed in the above solution for electrochemical measurement. The polarization curve and corrosion current density finally obtained are shown in Figures 6 and 7. At the same time, the corrosion rate of the substrate was calculated and analyzed by the weight loss method after immersion, and the results are shown in Figures 4 and 5.
[0043] Combining Figures 6 and 7, it can be seen that after adding silicon quantum dots, the corrosion current density of Q235 steel is getting lower and lower compared to the blank condition. This shows that the addition of silicon quantum dot corrosion inhibitor significantly delays the corrosion of carbon steel by corrosive media (hydrochloric acid, sodium chloride solution), and is a mixed corrosion inhibitor that mainly inhibits anodic corrosion. Its corrosion inhibition effect mainly depends on the formation of a physical barrier (hydrophobic protective layer) and the chemical adsorption produced by metal coordination-chelation interaction.
[0044] The silicon quantum dot water treatment agent prepared in Example 1 was added to the standard test solution, and the scale inhibitor solution with a concentration of 1, 2, 3, 4, 5, and 6 mg / L was used to inhibit calcium sulfate scale, and the scale inhibitor solution with a concentration of 5, 10, 50, 100, and 150 mg / L was used to inhibit calcium carbonate scale. The scale inhibition performance was tested according to the above-mentioned static scale inhibition test method, and the scale inhibition efficiency of the silicon quantum dot water treatment agent for calcium sulfate and calcium carbonate was finally obtained as shown in Figure 8.
[0045] In addition, this Example 1 also shows a scale diagram after the silicon quantum dot water treatment agent scale inhibition test. As shown in Figure 9, the silicon quantum dot water treatment agent can destroy the structure of calcium sulfate and calcium carbonate crystals, and the surface shape and particle size have changed, showing significant scale inhibition performance.
[0046] Example 6
[0047] When the modifier carboxymethyl cellulose (CAS: 9000-11-7) is directly used and the addition concentration reaches 18 mg / L, the inhibition efficiency of calcium sulfate scale reaches 78.05%, which has a certain inhibitory effect on the formation of calcium sulfate scale, and the scale inhibition performance is weaker than the silicon quantum dot water treatment agent of the present invention; when the addition concentration is 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 39.97% when immersed in a 0.5 mol / L HCl environment; when immersed in a 3.5wt.% NaCl solution, the corrosion inhibition efficiency reaches 43.16%; it has a certain inhibitory effect on the corrosion of hydrochloric acid and sodium chloride, and the corrosion inhibition performance is weaker than the silicon quantum dot water treatment agent of the present invention. In summary, the scale inhibition and corrosion inhibition performance of carboxymethyl cellulose are not as good as those of the silicon quantum dot water treatment agent of the present invention.
[0048] Example 7
[0049] According to the document published in 2024, "Carboxyl-Engineered Silicon Quantum Dots (CSiQDs) as an Efficient Scale Inhibitor: Formulation Inhibition Mechanism" (see Ismail, N., Alshami, A., Tikeri, G., Sun, D., Tayyebi, A., & Al-Goraee, AM, et al. (2024). Carboxyl-engineered silicon quantum dots (csiqds) as an efficient scale inhibitor: formulation inhibition mechanism. Industrial & Engineering Chemistry Research, 63 (16), 12.), carboxyl silicon quantum dots (CSiQDs) scale inhibitor was prepared. When the addition concentration reaches 20 mg / L, the inhibition efficiency of calcium sulfate scale reaches 100%, and it has a certain inhibitory effect on the formation of calcium sulfate scale, and the scale inhibition performance is weaker than the silicon quantum dot water treatment agent; when the addition concentration is 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 11.06% when immersed in 0.5 mol / L HCl environment; when immersed in 3.5wt.% NaCl solution, the corrosion inhibition efficiency reaches 13.52%; there is no obvious inhibitory effect on the corrosion of hydrochloric acid and sodium chloride, and the corrosion inhibition performance is weaker than the silicon quantum dot water treatment agent of the present invention. In summary, the scale inhibition and corrosion inhibition performance of CSiQDs reported in the literature are not as good as the silicon quantum dot water treatment agent of the present invention.
[0050] Example 8
[0051] According to the patent "Carboxymethyl cellulose-based sulfur quantum dot scale inhibitor" (CN202311546267.6) published in 2023, a carboxymethyl cellulose-based sulfur quantum dot scale inhibitor (CMC-SQDs) was prepared. When the addition concentration reaches 0.8 mg / L, the inhibition efficiency of calcium sulfate scale reaches 100%, and the scale inhibition performance is stronger than the silicon quantum dot water treatment agent of the present invention; however, when the addition concentration is 100 mg / L, the Q235 carbon steel is immersed in a 0.5 mol / L HCl environment, and the corrosion inhibition efficiency is only 0.23%, and there is no corrosion inhibition effect; immersed in a 3.5wt.% NaCl solution, the corrosion inhibition efficiency is only 4.01%, and it has no obvious inhibitory effect on the corrosion of hydrochloric acid and sodium chloride, and does not have corrosion inhibition performance. In summary, the CMC-SQDs reported in this patent have excellent scale inhibition performance, but it does not have corrosion inhibition performance. In contrast, the multifunctional silicon quantum dot water treatment agent of the present invention, which has both corrosion inhibition and scale inhibition properties, can achieve a better "one dose, multiple effects" technical effect.
[0052] Example 9
[0053] According to the document published in 2019, "Synthesis and application of CCQDs as a novel type of environmentally friendly scale inhibitor" (see: Hao, JianLi, LingyunZhao, WeiweiWu, XiaqianXiao, YangyangZhang, HongfengTang, NaWang,Xiaocong. (2019). Synthesis and application of ccqds as a novel type ofenvironmentally friendly scale inhibitor. ACS applied materials&interfaces,11(9).), carboxyl carbon quantum dot scale inhibitor (CCQDs) was prepared. When the addition concentration reaches 200 mg / L, the inhibition efficiency of calcium sulfate scale reaches 100%, and when the addition concentration reaches 20 mg / L, the inhibition efficiency of barium sulfate scale reaches 100%, and the scale inhibition performance is weaker than the silicon quantum dot water treatment agent of the present invention; when the addition concentration is 100 mg / L, the corrosion inhibition efficiency of Q235 carbon steel is 29.59% when immersed in 0.5 mol / L HCl environment, and there is no corrosion inhibition effect; when immersed in 3.5wt.% NaCl solution, the corrosion inhibition efficiency reaches 36.10%; it has a certain inhibitory effect on the corrosion of hydrochloric acid and sodium chloride, and the corrosion inhibition performance is weaker than the silicon quantum dot water treatment agent of the present invention. In summary, the scale inhibition and corrosion inhibition performance of CCQDs reported in the literature are not as good as the silicon quantum dot water treatment agent of the present invention.
[0054] Compared with the existing corrosion and scale inhibition technologies, silicon quantum dots have the characteristics of simple synthesis process, mild reaction conditions, easy-to-obtain raw materials, green, non-toxic and easily degradable synthetic products, and low raw material costs. In addition, the corrosion inhibition efficiency evaluation results of silicon quantum dots synthesized by hydrothermal method with trisodium citrate and carboxymethyl cellulose can reach more than 90%, the scale inhibition efficiency for calcium sulfate can reach more than 99%, and it also has a certain inhibitory effect on calcium carbonate.
[0055] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silicon quantum dot water treatment agent with corrosion and scale inhibition properties, characterized in that: The steps include: S1: Disperse the silicon source, modifier and reducing agent in ultrapure water, mix and stir for 35-55 minutes to obtain a mixed solution; S2: transferring the mixed solution obtained in step S1 to a reaction container for reaction to obtain a silicon quantum dot solution; S3: Centrifuge the silicon quantum dot solution obtained in step S2, purify, and freeze-dry to obtain a solid silicon quantum dot water treatment agent.
2. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 1, characterized in that: The mass ratio of the silicon source, the modifier and the reducing agent in step S1 is 5-7:1:1; the solid-liquid ratio of the silicon source and ultrapure water is 2-5g:10ml.
3. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 2, characterized in that: The silicon source is trimethylsilyl imidazole, the modifier is one of carboxymethyl cellulose, chitosan or gum arabic, and the reducing agent is trisodium citrate.
4. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 1, characterized in that: In step S2, the temperature is kept at 210-230° C. for 2-6 hours.
5. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 1, characterized in that: The characteristics of the silicon quantum dots in step S2 are: water-soluble silicon quantum dots that have completed carboxylation and hydroxylation, and a large number of -COOH and -OH groups are modified on the surface.
6. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 1, characterized in that: The process parameters of the centrifugation in step S3 are: centrifugal speed 5000-10000 rpm, centrifugal time 10-30 min.
7. The method for preparing a silicon quantum dot water treatment agent having corrosion and scale inhibition properties according to claim 1, characterized in that: The purification process in step S3 is: dialyzing for 24-36 hours using a dialysis bag with a cutoff of 800-1500 Da; the drying process is: drying at a temperature of -50°C for 48-60 hours.
8. The silicon quantum dot water treatment agent with corrosion and scale inhibition performance prepared according to any one of claims 1 to 7 is used for corrosion inhibition of carbon steel under neutral and acidic conditions, characterized in that: When Q235 carbon steel is in a 3.5wt% NaCl solution and a 0.5 mol / L HCl environment, a silicon quantum dot water treatment agent is applied to the surface of the metal substrate, and the dosage of the silicon quantum dot water treatment agent is 20-100 mg / L.
9. The silicon quantum dot water treatment agent with corrosion and scale inhibition performance prepared according to any one of claims 1 to 7 is used in a solution that is prone to calcium sulfate scale formation, characterized in that: In solutions that are prone to calcium sulfate scale formation, the dosage of silicon quantum dot water treatment agent is 0.5-6 mg / L.
10. The silicon quantum dot water treatment agent with corrosion and scale inhibition performance prepared according to any one of claims 1 to 7 is used in a solution that is prone to calcium carbonate scale formation, characterized in that: In solutions that are prone to calcium carbonate scale formation, the dosage of silicon quantum dot water treatment agent is 5-150 mg / L.
Citation Information
Patent Citations
Multifunctional cellulose-based sulfur quantum dot and application
CN117603678A
Preparation method of porous silicon base CdS quantum dot composite material
CN103087710A
Application of water-soluble silicon quantum dots as drug carriers
CN104306984A
Photocatalyst as well as preparation method and application method thereof
CN108855242A
Special nano-quantum-dot microcellular-foam jardiance medicine for diabetes and preparation method of special nano-quantum-dot microcellular-foam jardiance medicine for diabetes
CN109125279A